Kenyamanan Termal pada Taman Air Berarsitektur Tradisional Bali (Studi Kasus: Tirta Gangga) - I Wayan Wirya Sastrawan; I Gede Surya Darmawan; Ni Wayan Meidayanti Mustika (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2018)
Thermal comfort is an absolute for the human body, therefore human always attempting to customise the environment to achieve thermal convenience for the body. Water parks in this research are planned with the built environment applying the elements of the exterior space architecture supported the concept of traditional Balinese architecture. See the conditions, then there is an important opportunity and conducted research on the characteristics of the thermal comfort of the water garden. The focus of this research is the thermal comfort level and element of outdoor space in the garden Tirta Gangga, Karangasem. Taman Tirta Gangga was chosen as the locus of research because it has the characteristics of a typical application elements especially water parks that dominate and the application of the concept of traditional Balinese architecture. The purpose of this research was to identify the distribution of thermal conditions, knowing the level of influence of the outside space of the element against thermal conditions, and the extent of the impact of the pattern arrangement of water garden with traditional Balinese architecture concept against thermal comfort. So the results of this research can be used as a foundation for architects in developing and designing a water garden can function optimally. In this study using the method of comparison and simulation to see thermal comfort condition visualisation objects of research. From the results of the simulations can be used to identify the influence of the element of outdoor space and the concept of traditional Balinese architecture against the thermal comfort on the object of research. Kenyamanan termal menjadi hal yang mutlak bagi tubuh manusia, oleh karenanya manusia sesalu berusaha mengkondisikan lingkungan untuk mencapai kenyamana termal bagi tubuhnya. Salah satu tempat manusia beraktivitas adalah ruang luar. Taman air dalam penelitian ini merupakan lingkungan binaan terencana dengan mengaplikasikan elemen-elemen arsitetur ruang luar yang didukung konsep Arsitektur Tradisional Bali. Melihat kondisi tersebut, maka terdapat peluang dan penting dilakukan penelitian mengenai Karakteristik Kenyamanan Termal Taman Air. Fokus penelitian ini adalah tingkat kenyamanan termal dan elemen ruang luar di Taman Tirta Gangga, Karangasem. Taman Tirta Gangga dipilih sebagai lokus penelitian karena memiliki karakteristik yang khas terutama penerapan elemen taman air yang mendominasi serta penerapan konsep Arsitektur Tradisional Bali. Tujuan penelitian ini untuk mengidentifikasi sebaran kondisi termal, mengetahui tingkat pengaruh elemen ruang luar terhadap kondisi termal, dan sejauh mana pengaruh pola penataan taman air dengan konsep Arsitektur Tradisional Bali terhadap kenyamanan termal. Sehingga hasil penelitian ini dapat dijadikan landasan bagi arsitek dalam mengembangkan dan merancang Taman Air yang dapat berfungsi secara optimal. Dalam penelitian ini menggunakan metode komparasi dan simulasi untuk melihat visualisasi kondisi kenyamanan termal dalam obyek penelitian. Dari hasil simulasi tersebut dapat digunakan mengidentifikasi pengaruh elemen ruang luar dan konsep Arsitektur Tradisional Bali terhadap kenyamanan termal pada obyek penelitian.